# How do you simpilfy this equation?: a-b/b^2 / a^2-b^2/b

### 2 Answers | Add Yours

We can first factor the a^2 - b^2.

`((a - b)/(b^2))/(((a-b)(a+b))/b)`

When dividing rational expression we flip the bottom, and proceed on multiplication.

`((a - b)/b^2)/((a - b)(a + b)/b) = ((a - b)/b^2) *(b/((a - b)(a + b)))`

We can cancel common factor on top and bottom.

`((a - b)/b^2)*(b/((a - b)(a+b))) = 1/(b(a+b))`

Hence, **final answer is 1/(b(a + b))**.

`((a-b)/b^2)/((a^2-b^2)/b)= ` `(a-b)/b^2 xx b/((a+b)(a-b))=` `1/(b(a+b))`